The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1001/archpsyc.56.2.121
|View full text |Cite
|
Sign up to set email alerts
|

A 40-Year Follow-up of Patients With Obsessive-compulsive Disorder

Abstract: Background:The long-term course of obsessivecompulsive disorder is insufficiently known. We studied the course of this disorder in patients who were followed up for 40 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
209
2
17

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 522 publications
(241 citation statements)
references
References 31 publications
(34 reference statements)
11
209
2
17
Order By: Relevance
“…In another study from Italy, which included 55 outpatients with OCD treated with SSRIs, the rates for complete and partial remission at 3 years' follow-up were 22% and 34%, respectively. 92 The main conclusion that can be drawn from the above discussion is that remission rates in the modern era have not improved compared with those reported in earlier studies 88,89 despite the wide availability of effective treatments. It is difficult, however, to interpret this finding, as changes in diagnostic preferences or criteria may have resulted in non-comparable groups of patients being selected for inclusion in these studies.…”
Section: Natural History: Prognosismentioning
confidence: 86%
See 2 more Smart Citations
“…In another study from Italy, which included 55 outpatients with OCD treated with SSRIs, the rates for complete and partial remission at 3 years' follow-up were 22% and 34%, respectively. 92 The main conclusion that can be drawn from the above discussion is that remission rates in the modern era have not improved compared with those reported in earlier studies 88,89 despite the wide availability of effective treatments. It is difficult, however, to interpret this finding, as changes in diagnostic preferences or criteria may have resulted in non-comparable groups of patients being selected for inclusion in these studies.…”
Section: Natural History: Prognosismentioning
confidence: 86%
“…89,[92][93][94][95] In the Brown cohort, 91 patients with primary hoarding obsessions/ compulsions had a worse prognosis with very low remission rates, whereas patients with primary obsessions regarding an inflated sense of responsibility for harm had a better prognosis. In the Yale cohort, 90 an initial good response to SSRIs was a good prognostic factor.…”
Section: Natural History: Prognosismentioning
confidence: 99%
See 1 more Smart Citation
“…However, we know that the rate of improvement in OCD is limited. A naturalistic study [30]found that over a follow-up of 40 years, only 20% of 144 OCD patients had recovered. Our study showed at post-test (week 16) that about 16% of our sample had recovered and 20% at week 52.…”
Section: Discussionmentioning
confidence: 99%
“…Symptom exacerbations are frequent and only some patients achieve durable complete remission [9, 10, 11]. …”
Section: Introductionmentioning
confidence: 99%